Associations Between Adult Triceps Skinfold Thickness and All-Cause, Cardiovascular and Cerebrovascular Mortality in NHANES 1999–2010: A Retrospective National Study - Li, Weiya; Yin, Han; Chen, Yilin; Liu, Quanjun; Wang, Yu; Qiu, Di; Ma, Huan; Geng, Qingshan (Frontiers in Cardiovascular Medicine, 2022)
Background: The association between triceps skinfold (TSF) thickness and mortality in previous studies was controversial. This study aimed to explore how TSF thickness affects all-cause, cardiovascular, and cerebrovascular mortality among United States (U.S.) general population. Methods: Our research included 25,954 adults in the National Health and Nutrition Examination Survey (NHANES) from 1,999 to 2,010. Participants were categorized by the baseline TSF quartiles [Quartile1(Q1): <11.8, (Q2): 11.8-17.4, (Q3): 17.4-25, (Q4): ≥25; Unit: millimeter (mm)]. Cox regression models were used to assess the association of TSF with all-cause, cardiovascular and cerebrovascular mortality. The association between mid-arm muscle circumference (MAMC) and mortality was also explored. Subgroup analyses were conducted to assess heterogeneity in different subgroups. Results: The highest TSF group (Q4) had the lowest risk to experience all-cause (HR, 0.46; 95% CI, 0.38-0.59; P <0.001) and cardiovascular mortality (HR, 0.35; 95% CI, 0.23-0.54; P <0.001) than the lowest TSF group (Q1) after multivariate adjustment. However, there was no relationship between TSF quartiles and cerebrovascular mortality (HR, 0.98; 95%CI, 0.42-2.30; P =0.97). The protective effects of TSF thickness on the mortality were still existed after adjusting for BMI and MAMC. For every 1mm increase in TSF thickness, the risk of all-cause and cardiovascular death decreased by 4% (HR, 0.96; 95% CI, 0.95-0.97; P <0.001) and 6% (HR, 0.94; 95% CI, 0.93-0.96; P <0.001), respectively. In the stratified analysis, the relationships between TSF and mortality risk were generally similar across all subgroups. Conclusions: Higher TSF thickness was associated with lower all-cause as well as cardiovascular mortality, independent of BMI and MAMC. Our study revealed that the TSF thickness may be a convenient and credible indictor to predict mortality, especially in those with severe cardiovascular diseases.